2017
DOI: 10.3390/geosciences7040093
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-Based Photogrammetry Survey for Medieval Archaeology: Toward a 3D Geographic Information System (GIS)

Abstract: This paper presents certain reflections concerning an interdisciplinary project between medieval archaeologists from the University of Florence (Italy) and computer science researchers from CNRS, National Center for Scientific Research, (France), aiming towards a connection between 3D spatial representation and archaeological knowledge. We try to develop an integrated system for archaeological 3D survey and all other types of archaeological data and knowledge by incorporating observable (material) and non-grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This analysis confirmed that the study area was economically utilized almost during the whole studied period. The advantages of analyzing the historical, topographic maps and orthophotos for the research of archaeological findings were also pointed out in the works of Zupancich et al [44], Gennaro et al [45], Tache et al [46], Drap et al [47] and so on.…”
Section: Discussionmentioning
confidence: 95%
“…This analysis confirmed that the study area was economically utilized almost during the whole studied period. The advantages of analyzing the historical, topographic maps and orthophotos for the research of archaeological findings were also pointed out in the works of Zupancich et al [44], Gennaro et al [45], Tache et al [46], Drap et al [47] and so on.…”
Section: Discussionmentioning
confidence: 95%
“…Algorithmic segmentation uses mathematical rules and functions as constraints during the segmentation (and possibly also classification). These rules may range from simple rules (e.g., "floors are flat and located below each storey" or "pillars are cylinders") [25] to the implementation of ontological relations [41][42][43].…”
Section: Algorithmic Approachmentioning
confidence: 99%
“…Agapiou et al [8] 3278 1904 5 Agapiou et al [3] 1708 970 8 Chyla [9] 1429 827 1 Comer et al [5] 1570 1102 3 Corso et al [12] 1753 1215 2 Danti et al [10] 1943 1740 7 Drap et al [13] 1571 1565 2 Gade et al [6] 1751 1210 4 Garcia-Garcia et al [14] 1282 995 1 Guidi et al [15] 1719 976 3 Kalayci et al [16] 1218 968 2 Křivánek [17] 1420 1174 2 Malinverni et al [18] 1445 1345 1 Parcak et al [11] 1486 1374 3 Poux et al [19] 2306 2249 7 Rayne et al [7] 1750 1500 5 Rutishauser et al [4] 1784 1345 2 Sonnemann et al [20] 1582 1046 2 Tapete [1] 1256 2313 3 Traviglia & Torsello [2] 1680 1311 9 Verhoeven [21] 1573 1399 6 Building upon the positive outcome achieved in 2017 and in order to continue this Special Series, in March 2018 I launched the call for papers for a second edition of the Special Issue with the title "Earth Observation, Remote Sensing and Geoscientific Ground Investigations for Archaeological and Heritage Research".…”
Section: Authors Views Downloads Citationsmentioning
confidence: 99%